PERAMALAN JUMLAH PENDUDUK KOTA PASURUAN DENGAN MENGGUNAKAN METODE SINGLE DAN DOUBLE EXPONENTIAL SMOOTHING - Raihan Ihza Pravisya; Ahmad Rofiqul Muslikh (Fakultas Ilmu Komputer dan Desain - Unsurya, 2024)
This study aims to forecast the population of Pasuruan City using Single and Double Exponential Smoothing methods. Population forecasting is crucial for urban planning, economic development, and public services. Data from 2010 to 2022 provided by the Central Bureau of Statistics of Pasuruan City was utilized for this research. The Single Exponential Smoothing method demonstrated higher accuracy with lower Mean Squared Error (MSE) and Root Mean Squared Error (RMSE) values compared to the Double Exponential Smoothing method. Specifically, the MSE for the Single Exponential Smoothing method was 623,986,327,670, while the Double Exponential Smoothing method recorded an MSE of 1,269,743,472,543. The corresponding RMSE values were 7,899,281 and 11,268,289, respectively. The results indicate that the Single Exponential Smoothing method is more reliable for predicting the population trends in Pasuruan City.The findings of this research can aid local governments and policymakers in making informed decisions regarding resource allocation, infrastructure development, and social services. Future studies could consider incorporating external factors such as migration, birth rates, and government policies to enhance the accuracy of population forecasts.